Game Learning Astronomi Tebak Nama Planet Berbasis Android Dengan App Inventor 2 - M. Amar Ma’mun (Melek IT : Information Technology Journal, 2019)
Serious games are games that were developed with the aim of not only giving pleasure to players, but also claiming to have the aim of providing knowledge experiences to achieve learning goals through a guided environment and suggesting that games should have challenges for students who lack interest in learning about astronomy can always be interested use it. Now there are many games that are used as learning or education. Educational games are usually applied by age level or genre. The purpose of educational games can train thinking power, logic and interest in learning for elementary school students so that it can encourage students to increase their interest in learning about astronomy. The learning method using games is expected to be more interesting and easy to understand for the players, especially for elementary school students. The result of this writing is the android-based astronomy learning game "Guess the Name of the Planet" with the Inventor 2 app, from flowchart design to FSM of the game.